2016
DOI: 10.5194/acp-16-6285-2016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of built environment characteristics on urban boundary layer dynamics using an advanced stochastic approach

Abstract: Abstract. Urban land-atmosphere interactions can be captured by numerical modeling framework with coupled land surface and atmospheric processes, while the model performance depends largely on accurate input parameters. In this study, we use an advanced stochastic approach to quantify parameter uncertainty and model sensitivity of a coupled numerical framework for urban land-atmosphere interactions. It is found that the development of urban boundary layer is highly sensitive to surface characteristics of built… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The evolution of CO 2 concentration in the UBL is modeled by a single column atmospheric model (SCM) based on a modified K ‐theory [ Noh et al , ; Hong et al , ; Song and Wang , , , , ]. The governing turbulence diffusion equations in the SCM for a generic scalar atmospheric variable c in the UBL can be expressed by [ Song and Wang , ] ct=z()prefix−truewc¯ where t is the evolution time; z is the elevation above the land surface; w is the vertical wind speed; c could be temperature, humidity, or CO 2 concentration; and truewc¯ is the vertical kinematic flux of heat (if c is temperature), moisture (if c is humidity), and carbon dioxide (if c is CO 2 concentration) correspondingly.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The evolution of CO 2 concentration in the UBL is modeled by a single column atmospheric model (SCM) based on a modified K ‐theory [ Noh et al , ; Hong et al , ; Song and Wang , , , , ]. The governing turbulence diffusion equations in the SCM for a generic scalar atmospheric variable c in the UBL can be expressed by [ Song and Wang , ] ct=z()prefix−truewc¯ where t is the evolution time; z is the elevation above the land surface; w is the vertical wind speed; c could be temperature, humidity, or CO 2 concentration; and truewc¯ is the vertical kinematic flux of heat (if c is temperature), moisture (if c is humidity), and carbon dioxide (if c is CO 2 concentration) correspondingly.…”
Section: Methodsmentioning
confidence: 99%
“…The surface flux truewc¯0 at the lower boundary of the UBL is provided by EC measurements, while the upper boundary (entrainment) is prescribed as truewc¯e=prefix−βctruewc¯0 with β c as the empirical fraction, specifically β c = 0.1–0.3 for temperature [ Noh et al , ], β c = −1.0–0 for humidity [ de Arellano et al , ], and β c = −0.2–3.0 for CO 2 concentration [ de Arellano et al , ]. Specifically for Phoenix site, we used 0.2 as the entrainment rate of heat flux and 0.95 as the entrainment rate of moisture flux and CO 2 flux based on previous studies [ Song and Wang , , , , ]. Detailed parameterizations for UBL height, eddy diffusivity, velocity scale, and CO 2 flux within the UBL for both daytime and nighttime are described in Table [ Deardorff , ; Yu , ; Hong et al , ; Hong , ; Ouwersloot and Vilà‐Guerau de Arellano , ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies use a 3D set‐up, which limits the ability to link the model response to changes in surface parameters and investigate feedback mechanisms in detail. To circumvent this drawback, the SCM set‐up can be used (e.g., Song and Wang, ; ; Nemunaitis‐Berry et al . ), which allows for a detailed investigation of the model response to changes in surface parameters, while at the same time having a much lower computational cost than the 3D set‐up.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of excessively elevated temperature in city cores, as compared to their rural surroundings, is the main driver of many adverse urban environmental problems, ranging from thermal discomfort and human health (Kovats and Hajat, 2008), to building energy efficiency (Akbari and Konopacki, 2005; Wang et al, 2016), to air quality degradation (Taha, 1997; Sarrat et al, 2006). In addition, field observations as well as model simulations have shown that the UHI effect is often more prominent during nighttime (Chow et al, 2012; Song and Wang 2016a, b). This is especially true for densely built cities with downtown areas full of skyscrapers and narrow and deep street canyons (e.g.…”
Section: Introductionmentioning
confidence: 99%